2003
DOI: 10.3327/jnst.40.895
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Damage Formation up to over 10 Million Cycles Off-line Test by MIMTM

Abstract: A liquid-mercury target system for the MW-scale target is being developed in the world. The pitting damage induced by pressure wave propagation gets to be one of critical issues to estimate the life of the target structure with mercury and to evaluate its structural integrity. The off-line test on the pitting damage at high cycles over 10 millions was carried out using a novel device, the MIMTM which drives electromagnetically to impose pulse pressure into the mercury. It was found from the pitting damage data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 7 publications
3
47
0
1
Order By: Relevance
“…If the maximum depth of damage keeps increasing, more obvious differences were shown in the relatively lower frequency range. Cavitation damage develops from isolated micro localized damage to area erosion when the maximum depth increases up to approximately 15μm [16,17]. At this stage, the number of damage changed obviously while the maximum depth of damage almost keeps a constant.…”
Section: Damage Evaluation By Wdamentioning
confidence: 99%
“…If the maximum depth of damage keeps increasing, more obvious differences were shown in the relatively lower frequency range. Cavitation damage develops from isolated micro localized damage to area erosion when the maximum depth increases up to approximately 15μm [16,17]. At this stage, the number of damage changed obviously while the maximum depth of damage almost keeps a constant.…”
Section: Damage Evaluation By Wdamentioning
confidence: 99%
“…The number of impacts performed at each area was 0, 10 4 , 10 5 , 10 6 and 10 7 , respectively. The peak-to-peak (P-P) roughness of the cavitation damage at each area was: (I) 45 µm, (II) 35 µm, (III) 25 µm, (IV) 15 µm.…”
Section: Cavitation Damagementioning
confidence: 99%
“…8) As an engineering issue caused by a pressure wave, cavitation damage in liquid mercury targets raises a significant problem in the development of spallation neutron sources. [11][12][13][14][15] High-power pulsed spallation neutron sources are working in the Japan Proton Accelerator Research Complex (J-PARC) 16) and the Spallation Neutron Source (SNS) of the United States. 17) In both neutron sources, liquid mercury was selected as a target material because of its high neutron yield and high cooling performance.…”
Section: Mitigation Technologies For Damage Induced By Pressure Wavesmentioning
confidence: 99%
“…The pressure waves cause a serious issue for operational stability of the neutron sources because they induce the cavitation of mercury, which results in cavitation damage on the stainless steel target vessel and degrades its structural integrity. [11][12][13][14] In order to solve this critical issue, the authors investigated a surface improvement of the target vessel walls to mitigate damage formation due to cavitation bubble collapse. 13,18) However, it was found that long-range damage mitigation by the surface improvement is very difficult and, hence, some other treatments are required.…”
Section: Mitigation Technologies For Damage Induced By Pressure Wavesmentioning
confidence: 99%